Defining Journalism Innovation in Latin America: Exploration Into Perceptions Among Educators, Students, and Journalists. (December 2020) - Schmitz Weiss, Amy; de Macedo Higgins Joyce, Vanessa; Harlow, Summer; Alves, Rosental Calmon
Innovation is driving major changes in journalism globally. Understanding how journalism educators, students, and journalists perceive of innovation—in themselves and their organizations—is another layer by which to understand how the overall industry is evolving. This study explores the perceptions of innovation through an international survey ( N = 1, 543) of journalism educators, students, and journalists from Latin America. Findings show that journalists perceive themselves as more innovative than those in the academy. A significant gap appears between the academy and newsroom of how innovation is being defined and what it means to be innovative, which poses implications for the future of journalism students and journalists alike.